IMPLEMENTASI MANAJEMEN KEMAHASISWAAN DALAM MENDUKUNG TATA KELOLA PERGURUAN TINGGI ISLAM DI IAI NURUL HAKIM KEDIRI LOMBOK BARAT - Eva Zulfa; Halimatuzzahrah Halimatuzzahrah; Sunardi Sunardi (re-JIEM (Research Journal of Islamic Education Management), 2026)
Student management planning is an important aspect in supporting effective and sustainable Islamic higher education governance. This study aims to analyze the implementation of student management in supporting Islamic higher education governance at IAI Nurul Hakim Kediri, West Lombok. This study uses a qualitative approach with a case study type. Data were collected through in-depth interviews, observations, and documentation studies involving university leaders, student administrators, BEM advisors, and students. Data analysis was carried out interactively through data reduction, data presentation, and conclusion drawing, with data validity guaranteed through triangulation of sources and techniques. The results of the study indicate that the implementation of student management planning has been running, but not optimally. Planning is still adaptive and situational, implementation and evaluation are carried out naturally depending on conditions. The main obstacles found include unclear BEM budgets at the beginning of the period, weak coordination between BEM administrators and advisors, and the absence of a structured work program. This study is expected to add to the scientific knowledge of student management and serve as a consideration for more focused management of student organizations.